Kemitraan Antara Pemerintah Kota Pekanbaru dan Swasta Dalam Pengelolaan Sampah Pada Tahun 2018-2020 - Raihan Hasit; Hasim As'ari (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
Partnership between Pekanbaru City Government and the Private in Waste Management is a program planned by the Pekanbaru City Government which aims to assist the Pekanbaru City Government in carrying out the waste management process, in the waste management process in 2018-2020 divided into 3 zones, namely zone 1, Tampan District , Payung Sekaki, and Marpoyan Damai, zone 2 Sukajadi District, Senapelan, Pekanbaru Kota, Limapuluh, Sail, Bukit Raya and Tenayan Raya and zone 3 Rumbai and Rumbai Pesisir Districts. The research method used is descriptive qualitative method. The selection of informants uses purposive sampling technique. In collecting data, the authors use interview, observation and documentation techniques. The results of this study are the discovery of several facts that the Pekanbaru City Government is quite dependent on the private sector in the waste management process and the limited capacity of the Pekanbaru City Government in carrying out the management process. rubbish. The researcher also found several shortcomings that need attention to be improved, namely in the aspect of the existence of parties who are not included in the contract agreement between the Pekanbaru City Government and the private sector and suggestions or input from the private sector which are less appreciated so that the partnership program between the Pekanbaru City Government and the private sector is less run optimally.